KUALITAS PROSES AUDIT: TASK COMPLEXITY DAN LOCUS OF CONTROL DENGAN TABK SEBAGAI MODERASI - Elina, Jelita Frisca; Darmastuti, Dewi (Jurnal Aplikasi Akuntansi, 2024)
The COVID-19 pandemic has driven significant transformations in audit practices, particularly through the shift towards remote auditing. The focus of this research is to examine the influence of Task Complexity and Locus of Control on Audit Process Quality with Computer-Assisted Audit Techniques (CAAT) as a moderating variable. This study employs a quantitative research method with primary data collection through questionnaires and Likert scales. The research sample consists of 100 auditors working in Public Accounting Firms in DKI Jakarta, selected using purposive sampling method. Data analysis is conducted using Structural Equation Modeling (SEM) through the SmartPLS 4.0 program with a significance level of 0.05. Findings indicate that Task Complexity has a significant negative impact on Audit Process Quality, while Internal Locus of Control has a significant positive influence. Conversely, External Locus of Control does not significantly affect Audit Process Quality. CAAT as a moderating variable weakens the relationship between Task Complexity and Audit Process Quality. However, CAAT does not strengthen the relationship between Internal Locus of Control and Audit Process Quality, and it does not influence the relationship between External Locus of Control and Audit Process Quality. The implications of this research lie in a more comprehensive understanding of components influencing audit process quality, contributing to the enhancement of audit practices in the digital era.